Role of CNSs Conserved Distal Cis-Regulatory Elements in CD4 + T Cell Development and Differentiation - Long, Xunyi; Luo, Chen; Zhu, Zhengming (Frontiers in Immunology, 2022)
Naïve CD4+ T cells differentiate into diverse subsets of effector cells and perform various homeostatic and immune functions. The differentiation and maintenance of these different subsets are controlled through the upregulation and silencing of master genes. Mechanistic studies of the regulation of these master genes identified conserved and distal intronic regulatory elements, which are accessible subsets of conserved non-coding sequences (CNSs), acting as cis-regulatory elements in a lineage-specific manner that controls the function of CD4+ T cells. Abnormal CNS activity is associated with incorrect expression of master genes and development of autoimmune diseases or immune suppression. Here, we describe the function of several conserved, distal cis-regulatory elements at the Foxp3, Rorc, Il-4, Il-10 and Il-17 gene locus were shown to play important roles in CD4+ T cells differentiation. Together, this review briefly outlines currently known CNSs, with a focus on their regulations and functions in complexes modulating the differentiation and maintenance of various CD4+ T cells subsets, in health and disease contexts, as well as during the conversion of T regulatory cells to T helper 17 cells. This article will provide a comprehensive view of CNSs conserved distal cis-regulatory elements at a few loci that control aspects of CD4+ T cells function.